Democracy on the Five Star Movement's Rousseau platform. Issue 5 (19th October 2020) - Stockman, Caroline; Scalia, Vincenzo
ABSTRACT: The Five Star Movement, or M5S, is a popular anti-establishment, populist political party in Italy. One of its key features is the Rousseau platform, an online space designed to enable direct democracy. Named after the eighteenth century thinker Jean-Jacques Rousseau, it banks on the idea that the traditional state is corrupt, while the people's will can be more directly polled and executed as a governing force. However, Rousseau has also been critiqued for defending despotism and characterised as the enemy of liberty. This paper takes a closer look at Rousseau's 'Emile' and 'The Social Contract', and points out how a critical reading could raise questions about the platform's true meaning. The analysis focuses specifically on the illusion of autonomous choice and covert authoritarianism. The platform becomes a powerful tool of both preventive as well as repressive social control. As an anti-modern public sphere, it holds inherent threats to democracy itself.